2022
DOI: 10.1177/23743735221117926
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Colonography (CTC): Is It Really the Non-Invasive Option We Think It Is? A Patient Experience Study

Abstract: Aims: Computed tomography colonography (CTC) is seen as a more tolerable alternative to colonoscopy, but patients struggle with the steps required for optimal diagnostic imaging. This prospective study aims to understand the experience of patients undergoing CTC. Methods: A survey was completed by a convenience sample of patients before and after CTC over 7 months. The 13-item questionnaire covered pre-test information, overall and specific experience of the test. The responses were tabulated and analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Concerning abdominal discomfort, one study showed more than 50% of people undergoing CT colonoscopy experienced abdominal discomfort from gas insufflation contributing to difficulties completing the investigation [ 18 ], and 25% experienced this symptom 24 hours after colonoscopy [ 8 ]. Another study showed abdominal pain or discomfort during colonoscopy remained up to seven days and factors associated with discomfort included younger age, lower BMI, difficulty of examination and previous gynecopelvic surgery [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning abdominal discomfort, one study showed more than 50% of people undergoing CT colonoscopy experienced abdominal discomfort from gas insufflation contributing to difficulties completing the investigation [ 18 ], and 25% experienced this symptom 24 hours after colonoscopy [ 8 ]. Another study showed abdominal pain or discomfort during colonoscopy remained up to seven days and factors associated with discomfort included younger age, lower BMI, difficulty of examination and previous gynecopelvic surgery [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to colonoscopy, bowel preparation with dietary restriction and laxative intake must be adhered before testing and a rectal catheter to inflate air or carbon dioxide in colon is typically used during CT colonography. Experiences of diarrhea, abdominal pain and discomfort with gas insufflation were unveiled [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation